2017
DOI: 10.1007/s10620-017-4828-z
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Small Intestinal Bacterial Overgrowth by Glucose Breath Test and Coronary Artery Disease

Abstract: SIBO was found to be associated with CAD and with the number of coronary arteries involved in this study from a single tertiary center. Further studies are necessary to confirm the association of SIBO with CAD. In the presence of risk factors, patients with SIBO may benefit from assessment for CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
11
1
3
Order By: Relevance
“…Lastly, as Fialho et al [11] recognize, despite the association between SIBO and CAD demonstrated in this paper, no conclusions can be drawn about causality of the relationship. While the work by Ponziani et al linking SIBO and atherosclerosis through the vitamin K-dependent action of MGP suggests a causal relationship, elucidation of an underlying mechanism linking SIBO and CAD is absent in the present study.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…Lastly, as Fialho et al [11] recognize, despite the association between SIBO and CAD demonstrated in this paper, no conclusions can be drawn about causality of the relationship. While the work by Ponziani et al linking SIBO and atherosclerosis through the vitamin K-dependent action of MGP suggests a causal relationship, elucidation of an underlying mechanism linking SIBO and CAD is absent in the present study.…”
contrasting
confidence: 70%
“…In the current issue of Digestive Diseases and Sciences, Fialho et al [11] expand upon this work by demonstrating a previously undescribed association between SIBO and coronary artery disease (CAD). In their study, they retrospectively reviewed medical records at a single tertiary care center in order to identify all patients who underwent a glucose hydrogen/methane breath test.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…There have been studies documenting that the alteration in the number/composition of gut-resident bacteria may be associated with the increased risk of development of CAD. In a retrospective study, the data from 1059 patients revealed that patients with small intestinal bacterial overgrowth had a higher frequency of CAD [22]. A comparative study conducted in CAD patients (n = 39) and healthy volunteers (n = 50) revealed a characteristic change in the gut microbiota.…”
Section: Gut Microbiota Composition and Its Possible Use As A Non-invmentioning
confidence: 99%
“…Так, в недавнем исследовании A. Fialho и соавт. было продемонстрировано, что наличие избыточного бактериального роста в тонкой кишке (СИБР) может служить независимым фактором риска развития ИБС [2]. В 2011 г.…”
unclassified